New Species of Lipinia (Squamata: Scincidae) from Borneo, Revealed by Molecular and Morphological Data - Das, I.; Austin, C.C (Society for the Study of Amphibians and Reptiles, 2007)
ABSTRACT.—A new species of scincid lizard of the genus Lipinia is described from isolated localities in Borneo, from Sabah, Sarawak, and Kalimantan. The species was formerly allocated to Lipinia quadrivittata (Peters, 1867), a species known from the southern Philippines and Sulawesi in eastern Indonesia